2016
DOI: 10.2118/170685-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Confinement on Pressure/Volume/Temperature Properties of Hydrocarbons in Shale Reservoirs

Abstract: Shale reservoirs play an important role as a future energy resource of the United States. Numerous studies were performed to describe the storage and transport of hydrocarbons through ultrasmall pores in the shale reservoirs. Most of these studies were developed by modifying techniques used for conventional reservoirs. The common pore-size distribution of the shale reservoirs is approximately 1 to 20 nm and in such confined spaces that the interactions between the wall of the container (i.e., the shale and ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 32 publications
2
89
2
Order By: Relevance
“…At the smallest pore radius (10 nm in pore diameter), the shifts in critical points for methane and ethane are noticeable but relatively modest. 45,56 220 For binary systems, MPTA+DRA shows the best prediction for the adsorbed amount with an AAD of 17.9% followed by ML and IAST+Langmuir with 26.1% and 27.0%, respectively. However, IAST+Langmuir shows a slightly better prediction for the composition in the adsorbed phase.…”
Section: Influence Of Adsorption Film On Phase Behaviormentioning
confidence: 99%
“…At the smallest pore radius (10 nm in pore diameter), the shifts in critical points for methane and ethane are noticeable but relatively modest. 45,56 220 For binary systems, MPTA+DRA shows the best prediction for the adsorbed amount with an AAD of 17.9% followed by ML and IAST+Langmuir with 26.1% and 27.0%, respectively. However, IAST+Langmuir shows a slightly better prediction for the composition in the adsorbed phase.…”
Section: Influence Of Adsorption Film On Phase Behaviormentioning
confidence: 99%
“…The degree of uncertainty is even larger when more than one component is present. Didar and Akkutlu 9 and Pitakbunkate et al ( 10 ) studied mixtures of hydrocarbons in which one component had a higher relative affinity for the surfaces of nanotubes. The researchers found that the properties of the mixtures were highly correlated with the degree of confinement.…”
Section: Introductionmentioning
confidence: 99%
“…While shale nanopores are both rough and irregular, smooth graphite slit pore models have been widely used as a simplified corollary for kerogen nanopores in shale [70][71][72] . Surface roughness affects both the flow dynamics and the adsorption capacity of methane in pores [73][74][75][76] .…”
Section: Methodsmentioning
confidence: 99%